Penerapan Manajemen Risiko Berbasis ISO 31000 Pada Bisnis Glow Chain - Haura Nurul Ilmi; Tariza Mega Pratiwi Garini; Naura Rahadhatul Aisy; Aulia Silvana; Alfiana (Indo Publishing, 2025)
This qualitative research applies ISO 31000 to analyze risk management in the Glow Chain accessory MSME (custom 3D beaded design products). The identification 25 potential risks (operational, market, financial, and human resources). Four risks are classfied as High (e.g., Rapid Changes in Accessory Trend (P9) and errors in Custom Order Fulfillment (P5)). This study proposes specific treatment actions (such a double verification for P5) to minimize the impacts and ensure the business continuity Glow Chain.